The Liability of the Air Carrier for Psychological Damage to the Traveler in Accordance with the Warsaw Treaty of 1929 and Developments in its Judicial Interpretation - Hussain, Zubair Mustafa; Qader, Wadah Ghassan Abdel (Journal of Legal and Political Studies, 2016)
"Warsaw –article 17- and Montreal Convention –article 17 sub-section 1- have adopted the compensation for Personal Injury of the passengers in the event of the international carriage by air. Despite the clarity of both articles concerning the compensation for these damages, jurisprudence and judges have considered the article 17 of Warsaw Convention open to interpretation concerning the pure psychiatric injuries. Although the Montreal convention had closed the door for such interpretation, its field is still clear according to article 33 of this convention. We try to highlight the Psychiatric Injuries that compensable, and we have presented our perspectives of the possibility of compensation the Psychiatric Injuries under the international carriage by air. We have given examples for such injuries such as sexual harassment, airplanes hijack, and Terrorist incidents. We have addressed a question to the Iraqi jurisprudence and judicial about: Why do we deny the compensation for psychiatric injuries in the contractual liability? Then we reveal the modern interpretation of Warsaw Convention concerning the accident that is been responsible by the carrier, and we have concluded the paper by revealing the air carrier liability and the methods for exceeding the liability."
Keywords: Montreal Convention; compensation ,Personal Injury; interpretation